2011
DOI: 10.1016/j.neuron.2011.05.014
|View full text |Cite
|
Sign up to set email alerts
|

Frontal Cortex and Reward-Guided Learning and Decision-Making

Abstract: During decision making, individuals are prone to rely on external cues such as expert advice when the outcome is not known. However, the electrophysiological correlates associated with outcome uncertainty and the use of expert advice are not completely understood. The feedback-related negativity (FRN), P3a, and P3b are event-related brain potentials (ERPs) linked to dissociable stages of feedback and attentional processing during decision making. Even though these ERPs are influenced by both reward-and punishm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

71
835
6
5

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 976 publications
(917 citation statements)
references
References 118 publications
71
835
6
5
Order By: Relevance
“…That is, participants who generally played more often showed, as expected, increased activation in VS, but also increased activation in medial PFC after rewards compared to losses. Previous studies demonstrated that activation in medial PFC regions during decision-making was related to increased risk-taking tendencies (Van Leijenhorst, Gunther Moor, et al, 2010;Xue et al, 2009;but see Eshel, Nelson, Blair, Pine, & Ernst, 2007), which is consistent with its role in reward-related action tendencies (Rushworth et al, 2011;Rushworth et al, 2012). The current study extends previous findings by showing that medial PFC activation during outcome processing was positively related to the tendency to choose a risky option in a cross-sectional sample.…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…That is, participants who generally played more often showed, as expected, increased activation in VS, but also increased activation in medial PFC after rewards compared to losses. Previous studies demonstrated that activation in medial PFC regions during decision-making was related to increased risk-taking tendencies (Van Leijenhorst, Gunther Moor, et al, 2010;Xue et al, 2009;but see Eshel, Nelson, Blair, Pine, & Ernst, 2007), which is consistent with its role in reward-related action tendencies (Rushworth et al, 2011;Rushworth et al, 2012). The current study extends previous findings by showing that medial PFC activation during outcome processing was positively related to the tendency to choose a risky option in a cross-sectional sample.…”
Section: Discussionsupporting
confidence: 52%
“…We, however, did not observe brain activation in a more ventral region of the medial PFC or the adjacent orbital frontal cortex. Given that these regions have been related to the representation and the comparison of value during risky choice (Kuhnen & Knutson, 2005;Rushworth et al, 2011), it may be that these regions are more readily activated in response to choice than outcome processing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our meta-analysis first identified a consistent involvement of the VS and vmPFC in downward comparison. Based on the role of these regions in reward processing [Carlson et al, 2011;Cromwell et al, 2005;McClure et al, 2004;Rushworth et al, 2011;Sescousse et al, 2015], our findings dovetail with the notion that downward comparison is experienced as rewarding [Bault et al, 2011;Dvash et al, 2010;Fliessbach et al, 2007]. Prior studies have shown the involvement of the VS in the processing of other types of social rewards, including good reputation [Izuma et al, 2008;Meshi et al, 2013] and social approval [Izuma et al, 2010].…”
Section: Discussionsupporting
confidence: 85%
“…Although the terms ‘reinforcement,’ and ‘reward’ are often used interchangeably, these terms have discrete behavioral definitions, and describe largely distinct neurobiological processes. Indeed, there are multiple constructs mediated by the mesolimbic system, and at least four such systems have been described in depth in numerous seminal reviews [39-43]: 1) reward motivation, also termed anticipation (typically subsuming what is colloquially described as ‘wanting,’) refers to processes that facilitate anticipation of reward and approach behaviors towards biologically relevant goals, including reward valuation, willingness to expend effort to obtain rewards, reward prediction, and reward-based decision-making [44]; 2) reward outcome (or the hedonic responses widely referred to as ‘liking’ or ‘pleasure’) includes both consummatory behaviors during reward obtainment and the processes associated with regulation of such behaviors [45]; 3) reward learning includes reward processes that shape the experience-dependent learning that guides future behaviors [46]; and 4) reward-related habitual behavior reflects those processes that are initiated based on reward feedback, but that persist even in the absence of such feedback [47,48]. …”
Section: Reviewmentioning
confidence: 99%